OXIDATION KINETICS AND QUANTIFICATION METHOD OF CHOLESTEROL USING CHOLESTEROL OXIDASE ENZYME CATALYST - Iip Izul Falah; Ritmaleni Ritmaleni; M. Utoro Yahya (Indonesian Journal of Chemistry, 2010)
In view of health, cholesterol is believed as one of many sources can raise several diseases. Hence, both of research in quantification and developing simple, rapid and accurate analysis method of cholesterol in a sample is very important. Aim of this research was to investigate cholesterol oxidation kinetics and its quantification method based on oxidation of cholesterol and formation complex compound of hexathiocyanato ferat(III), {Fe(SCN)6}-3. The kinetics analysis and quantification, involved cholesterol oxidation in 0.1 M and pH 7.0 phosphate buffer solution to produce cholest-4-en-3-one and hydrogen peroxide, in the presence of cholesterol oxidase enzyme. The formed hydrogen peroxide was used to oxidize iron(II) ion, which was reacted furthermore with thiocyanate ion to raise the red-brown complex compound. Results of the study showed that the complex was stable at 10-120 min since the reaction was started, with maximum wavelength of 530-540 nm. While the kinetics analysis gave first order oxidation reaction with a reaction rate constant, kapp = 5.22 x 10-2 min-1. Based on this kinetics data, cholesterol analysis method could be developed i.e. by oxidizing cholesterol within 1.5 h using cholesterol oxidase as a catalyst, and then reacted with Fe2+, in a solution containing thiocyanate ion. Absorbencies of solutions of the complex compound, measured at wavelength of 535 nm, were linearly proportional to their cholesterol concentrations, in the range of 50-450 ppm.